Pengaruh Penambahan Direct Fed Microbials Lokal Pada Domba Betina Lepas Sapih Terhadap Pertambahan Bobot Badan Harian, Konsumsi Pakan, dan Konversi Pakan - Isma Salsabila Rahmawati; Pambudi Yuwono; Juni Sumarmono (LPPM Perjuangan University of Tasikmalaya, 2023)
This study aims to determine the effect of probiotics on PBBH, feed consumption and feed conversion of lamb female Priangan. The research was conducted from November 16, 2021 to January 8, 2022 at LTW Tasikmalaya, West Java. The material was used 18 of female Priangan lamb aged 6 months. The study was conducted with 3 treatments and 6 replications. The treatments include P0 = concentrate + forage; P1 = concentrate + forage + 1% probiotics; P2 = concentrate + forage + 2% probiotics. The observed variables were average daily gain (ADG), feed consumption, and feed conversion. The data obtained were statistically processed using analysis of variance in a completely randomized design (CRD). The results showed that the highest average ADG in the control treatment was 26.00 ± 1.28 grams. The results of the analysis of the addition of probiotics to feed consumption in the form of dry matter, the highest was P2 of 346.73 ± 13.60 grams. The feed conversion calculation results at P2 showed higher results compared to P0 and P1, namely 14.20 ± 0.75. Based on the results of the study it can be concluded that the addition of probiotic products from LTW Tasikmalaya farms has a significant effect on ADG, feed consumption, and feed conversion. The results of the analysis showed that the administration of probiotics with higher concentrations, the resulting ADG decreased while feed consumption and feed conversion increased. Increased feed conversion indicates a lack of efficiency of feed absorbed by the body.